Open access and research dissemination in Africa - (:unkn) unknown (My University, 2020)
This paper discusses research undertaken by the Curtin Open Knowledge Initiative (COKI) andparticipants during and following an Open Knowledge international workshop held in Mauritiusin September 2019. The workshop brought together key experts to explore the role of openknowledge in the creation of equitable and inclusive global knowledge landscapes. This paperexplores the role of open access and institutional repositories in knowledge sharing and thedissemination of research output from higher education and research institutions within theAfrican continent. The paper reviews the landscape of research output from the Africancontinent; analyses open access research output, overviews of institutional knowledge sharingpositions and the dissemination of research output from Ghana, Rwanda, South Africa andUganda.
Keywords: African Research